Most Frequently Extracted Primary Tooth in Maxillary Arch of Children Visiting A University Hospital In Chennai: A Retrospective Study - Azima Hanin S.M1 , Geo Mani2 , Hemavathy Muralidoss3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Early or premature loss is defined as the loss of a deciduous tooth before its time of natural exfoliation.Thedisruption in the normal physiological process of deciduous tooth exfoliation and eruption of its successormay cause a series of changes in the dental arches ranging from a change in arch length to malocclusion ofsuccessive teeth. Premature loss of teeth can adversely affect oral health-related quality of life in children. The main aim of this study was to investigate the most frequently extracted maxillary primary tooth inchildren aged 1-15 years in Chennai, Tamil Nadu. This retrospective study was conducted among pediatricpatients who visited the OP of a university teaching hospital in Chennai during the period of June 2019 toMarch 2020. The collected data was then subjected to statistical analysis using Statistical Package for SocialScience (SPSS). Descriptive statistics and Chi square tests were used. The most frequent age group wasthe 7-12 years age group with 61.5% of the total population. Exodontia was most frequently seen in boyswith 53.9% of the total population.The most frequently extracted teeth was maxillary first right primarymolar with 17.8% followed by maxillary first left primary molar with 16.1%.Maxillary central incisors wasthe most frequently extracted teeth in younger age group 1-6 years with right primary maxillary centralincisor 8.33% and maxillary left primary central incisor 7.95% of total population. Within the limits of thestudy,Most frequently extracted tooth in the maxillary arch was the first primary molar. Exodontia was moreprevalent in the age group of 7-12 years. The most frequently extracted tooth in the younger age group (1-6years) was found to be the central incisors.